Linear change and minutes variability of solar wind velocity revealed by FAST. Issue 3 (22nd July 2022) - Liu, Li-Jia; Peng, Bo; Yu, Lei; Liu, Bin; Lu, Ji-Guang; Yu, Ye-Zhao; Xi, Hong-Wei; Xiong, Ming; Chang, O
ABSTRACT: Observation of Interplanetary Scintillation (IPS) provides an important and effective way to study the solar wind and the space weather. A series of IPS observations were conducted by the Five-hundred-meter Aperture Spherical radio Telescope ( FAST ). The extraordinary sensitivity and the wide frequency coverage make FAST an ideal platform for IPS studies. In this paper, we present some first scientific results from FAST observations of IPS with the L -band receiver. Based on the solar wind velocity fitting values of FAST observations on 2020 September 26–28, we found that the velocity decreases with increasing frequency linearly, which has not yet been reported in literature. And we have also detected a variation of solar wind velocity on a time-scale of 3–5 min, which imply the slow change of the background solar wind, a co-existence of high- and low-speed streams, or a reflect of the quasi-periodic electron-density fluctuations.